Regional convergence in Spain, 1980-2003: sectoral efficiency and productive structure (2012)
In this paper we review and update the evolution of regional economic disparities during the period 1980 2003, from the decomposition of VABpc in apparent labor productivity, employment per inhabitant, apparent productivity of capital and capitalization of employment, trying to identify the possible causes that have determined them, on the other hand, we examine the influence that restructuring of the productive sectors and sectoral productivity regions have had on the evolution of regional economic disparities, and finally we study the impact that capitalization of employment has had on production efficiency, and through it, at the level of economic development of the Spanish autonomous communities.